Counteracting effects on free radicals and histological alterations induced by a fraction with casearins - Ferreira De Araujo, Everton Jose; Lopes De Oliveira, Guilherme Antonio; De Sousa, Livia Queiroz; Bolzani, Vanderlan Da Silva [UNESP]; Cavalheiro, Alberto Jose [UNESP]; Tome, Adriana Da Rocha; Peron, Ana Paula; Dos Santos, Andre Gonzaga [UNESP]; Das Gracas Lopes Cito, Antonia Maria; Pessoa, Claudia; De Freitas, Rivelilson Mendes; Pinheiro Ferreira, Paulo Michel (Acad Brasileira De Ciencias, 2015)
Casearia sylvestris Swartz is a medicinal plant widely distributed in Brazil. It has anti-inflammatory, antiulcer and antitumor activities and is popularly used to treat snakebites, wounds, diarrhea, flu and chest colds. Its leaves are rich in oxygenated tricyclic cis-clerodane diterpenes, particulary casearins. Herein, we evaluated the antioxidant activities of a fraction with casearins (FC) isolated from C. sylvestris and histological changes on the central nervous system and livers of Mus musculus mice. Firstly, in vitro studies (0.9, 1.8, 3.6, 5.4 and 7.2 mu g/mL) revealed EC50 values of 3.7, 6.4 and 0.16 mu g/mL for nitrite, hydroxyl radical and TBARS levels, respectively. Secondly, FC (2.5, 5, 10 and 25 mg/kg/day) was intraperitoneally administered to Swiss mice for 7 consecutive days. Nitrite levels in the hippocampus (26.2, 27.3, 30.2 and 26.6 mu M) and striatum (26.3, 25.4, 34.3 and 27.5 mu M) increased in all treated animals (P < 0.05). Lower doses dropped reduced glutathione, catalase and TBARS levels in the hippocampus and striatum. With the exception of this reduction in TBARS formation, FC displayed only in vitro antioxidant activity. Animals exhibited histological alterations suggestive of neurotoxicity and hepatotoxicity, indicating the need for precaution regarding the consumption of medicinal formulations based on Casearia sylvestris.
Keywords: Clerodane diterpenes; Casearia sylvestris; antioxidant; morphological changes; toxicity